2016
DOI: 10.4103/2008-7802.174893
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life among people participating in a metabolic syndrome e-screening program: A web-based study

Abstract: Background:Cardiovascular diseases remain the leading cause of death worldwide. Metabolic syndrome (MetS) is the clustering of risk factors for developing the disease. Strong evidence exists for the efficacy of screening for MetS. However, the potential of novel web-based studies for MetS and online assessing of the quality of life (QOL) for these high-risk participants have not been explored.Methods:This was a web-based, cross-sectional study. Participants were recruited through online registering on the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…A large body of research found that people with MetS report lower HRQOL than people without MetS. 12 , 14 , 47 Our results were consistent with other studies. 48 , 49 Oh et al 48 reported that therapeutic lifestyle modification had been resulted in greater improvements in physical function ( P =0.017), general health ( P =0.001), vitality ( P =0.008) and mental health ( P =0.027).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A large body of research found that people with MetS report lower HRQOL than people without MetS. 12 , 14 , 47 Our results were consistent with other studies. 48 , 49 Oh et al 48 reported that therapeutic lifestyle modification had been resulted in greater improvements in physical function ( P =0.017), general health ( P =0.001), vitality ( P =0.008) and mental health ( P =0.027).…”
Section: Discussionsupporting
confidence: 91%
“…12 Several components of MetS such as abdominal obesity, hypertension and diabetes have been associated with lower HRQOL. 13 , 14 In line with this evidence Ford and colleagues indicated that of five components of MetS abdominal obesity and hyper trigliceridemia showed inverse association with HRQOL. 15…”
Section: Introductionmentioning
confidence: 79%
“…Previous study also reported lower health-related QoL level in people with metabolic syndrome. 42 QoL level was also negatively correlated with the level of CRP. This may be interpreted as an elevation in CRP level due to stress reaction 4 or a reduced QoL due to a worsening of medical condition.…”
Section: Discussionmentioning
confidence: 89%
“…Jahangiri et al demonstrated negative relationship between HRQOL and MetS. They declared that abdominal obesity and high blood pressure are associated with lower HRQOL in the participants with MetS [12]. Tsai et al revealed that participants with MetS had lower scores on physical function and general health [37].…”
Section: Discussionmentioning
confidence: 99%
“…The third report of the National Cholesterol Education Program Adult Treatment Panel III (ATP III) recognized the metabolic syndrome as a secondary target of risk-reduction therapy [11]. On the other hand, the negative effect of MetS on Health-Related Quality of life (HRQOL) have been reffered to in some studies [12, 13]. However, the quality of life status in veterans with or without metabolic syndrome has not been explored completely among the so called population.…”
Section: Introductionmentioning
confidence: 99%